Internalisasi Nilai Tasamuh dalam Tubuh Organisasi Masyarakat pada Ormas NU, Muhammadiyah dan LDII di Desa Jogoroto - Sayidah Afyatul Masruroh (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
The diversity of Islamic mass organizations in Indonesia causes different interpretations of many things, especially those related to religious matters which are not the main religious law. In reality these differences are not used as a basis for mutual understanding, but are exacerbated so as to ultimately lead to internal conflict. We should be concerned that awareness of internal tolerance cannot run well and lasts endlessly. Hopes of peace and harmony in Islam will be answered if we look at the village of Jogoroto, Jogoroto District, Jombang Regency. This article focuses on how to Internalize Tasamuh Values in Community Organizations. This research uses a descriptive qualitative approach. And the findings obtained are that the Internalization of Tasamuh Values in the Body of Community Organizations in Jogoroto Village is manifested in their daily behavior which always puts tolerance in social life, and that has become a culture. They argue that fellow Muslims are brothers, if there is a Muslim who is hurt then other Muslims will feel it.